2020
DOI: 10.37880/cumuiibf.745861
|View full text |Cite
|
Sign up to set email alerts
|

Sağlik Eği̇ti̇mi̇ Alan Öğrenci̇leri̇n Covi̇d-19 Salginina Yöneli̇k Algilarinin Değerlendi̇ri̇lmesi̇

Abstract: Bu çalışma, sağlık eğitimi alan öğrencilerin Covid-19 ile ilgili bilgi, tutum ve davranışlarını belirlemek amacıyla yapılmıştır. Çalışmanın ilk aşamasında oluşturulan 47 maddelik madde havuzundan uzman görüşü doğrultusunda 10 madde çıkarılmıştır. Öğrencilere 37 maddeden oluşan bir veri toplama aracı uygulanmış ve elde edilen veriler analiz edilmiştir. İlk aşamada açıklayıcı faktör analizi uygulanmıştır. KMO değeri 0,807, Barlett testi skoru 3517,143 (p<0,000) olarak hesaplanmış ve verilerin analize uygun olduğ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…In producing these metaphors, it can be said that the students commented on the decision of the schools to open on 4 January 2021 and had the perception of continuity of the precautionary rules in the school after it was opened. In the same way, Arslan and Filiz (2020) concluded that the students are aware of compliance with the measures taken by the state and fulfilling their individual responsibilities in their studies on COVID-19 perceptions.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In producing these metaphors, it can be said that the students commented on the decision of the schools to open on 4 January 2021 and had the perception of continuity of the precautionary rules in the school after it was opened. In the same way, Arslan and Filiz (2020) concluded that the students are aware of compliance with the measures taken by the state and fulfilling their individual responsibilities in their studies on COVID-19 perceptions.…”
Section: Discussionmentioning
confidence: 83%
“…This supports students to consider the school risky in this process. In addition, evaluating the perceptions of students who are having education in “health” regarding the COVID-19 pandemic, the study concluded that students had high concerns about the spread of the virus ( Arslan and Filiz, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sağlık hizmetleri için yapılan harcamalar, iyi bir refah düzeyinin yakalanması için büyük bir yatırımdır. Sağlık harcamaları tüm dünyada giderek artmakta ve önemli bir konu olmaktadır(Arslan & Filiz, 2020). COVİD-19 salgını ile sağlık yatırımlarının ve sağlık hizmetleri sunumunda kullanılan fiziksel ve beşerî kaynakların önemi bir kez daha ortaya çıkmıştır.…”
unclassified